The Existence of Higher Education (Public Relations, Competitiveness and Quality Assurance System) - Sumarto Sumarto (International Journal of Southeast Asia, 2023)
This paper conveys about the Existence of Higher Education through Public Relations, Competitiveness and Quality Assurance Systems. Higher Education cannot develop and advance without these three factors, Higher Education cannot possibly grow on its own, become great on its own without involving the community, competitiveness and quality that are continuously improved. The research methodology used in this paper is a Literature Study with Content Analysis from various Literature on the Existence and Role of Higher Education. The results and discussion in this study are that the existence of higher education can be achieved if it is carried out by strengthening public relations with community service activities and public relations activities. Improving Competitiveness by producing Graduates who are Professional, Skilled and Ready to Work. Improving the Quality of Higher Education in a sustainable manner in accordance with the times. Higher Education has many positive impacts on the community environment with the ability to produce graduates who are ready to work, graduates who are professional at work, graduates who are capable of being mobilizers in the community and graduates who have personalities that can be role models.